Evaluating deviations in prostatectomy patients treated with IMRT - Sá, Ana Cravo (2016)
Aim - To evaluate the deviations in prostatectomy patients treated with IMRT in order to calculate appropriate margins to create the PTV. Background - Defining inappropriate margins can lead to underdosing in target volumes and also overdosing in healthy tissues, increasing morbidity. Material and methods - 223 CBCT images used for alignment with the CT planning scan based on bony anatomy were analyzed in 12 patients treated with IMRT following prostatectomy. Shifts of CBCT images were recorded in three directions to calculate the required margin to create PTV. Results and discussion - The mean and standard deviation (SD) values in millimetres were −0.05 ± 1.35 in the LR direction, −0.03 ± 0.65 in the SI direction and −0.02 ± 2.05 the AP direction. The systematic error measured in the LR, SI and AP direction were 1.35 mm, 0.65 mm, and 2.05 mm with a random error of 2.07 mm; 1.45 mm and 3.16 mm, resulting in a PTV margin of 4.82 mm; 2.64 mm, and 7.33 mm, respectively. Conclusion - With IGRT we suggest a margin of 5 mm, 3 mm and 8 mm in the LR, SI and AP direction, respectively, to PTV1 and PTV2. Therefore, this study supports an anisotropic margin expansion to the PTV being the largest expansion in the AP direction and lower in SI.